Kesohihan Akidah Di Luar Empirisme: Menjawab Kritik Guru Gembul Melalui Metode Rasional Dan Kausalitas - Hadi, Bagus Kusumo; Dewi Setia Wati; Muhammad Alvin Saputra; Abdul Qodir Zaelani; Hadi, Dino Gautman Raharjo (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2024)
This study explores the critique of empiricism toward Islamic creed (akidah) as presented by Jafar Rohadi (known as Guru Gembul), who argues that faith, creed, and the concept of divinity are unscientific and subjective because they cannot be empirically proven. Guru Gembul's views on creed are framed as a product of secular epistemological hegemony, which limits knowledge to sensory experience. Through a qualitative-descriptive method based on literature review, this study compares the empiricist perspective with rational arguments from both Muslim and Western philosophers, such as Imam Al-Ghazali and Ramadhan Al-Buthi, who assert that scientific proof is not limited to empirical methods but also includes logic and causality. The study concludes that a rational approach is valid for scientifically proving the Islamic creed and that empiricism has limitations in explaining metaphysical reality. The implications of this research are to broaden the scope of scientific proof to encompass a rational understanding of Islamic creed and to enrich philosophical studies on faith within the context of scientific knowledge. Keywords: Guru Gembul, creed (akidah), scientific proof, empirical method, rational method, causality, Islamic philosophy